Persuasive copywriting : using psychology to influence, engage and sell - Maslen, Andy (Kogan Page, 2015)
Introduction: how to write like an angel and sell like a demon -- Harnessing the power of emotional copywriting to persuade your prospects -- Three big ideas you should use before benefits -- A powerful process for developing customer empathy -- Flattery will get you everywhere -- The ancient Greek secret of emotionally engaging copy -- Copywriting and connecting on social media -- Yes! I want your tips on the best way to ask for the order -- Five pleasure-inducing techniques for copywriters -- How to engage your imagination and free your creativity -- Finding your voice (and that of others) -- The definitive way to judge when grammar matters in copywriting -- An age-old method of injecting life into your sales pitch